Sistem Pendukung Keputusan Penentuan Penerimaan Bantuan Simpatik Guru Menggunakan Metode AHP dan SAW - Firdha Aprilyani (LPPM STMIK ANTAR BANGSA, 2020)
Abstract— PPPA Daarul Qur'an is an organization that manages almsgiving, devotes itself to community development based on the Qur'an, and is managed professionally. One of the programs in PPPA Daarul Qur'an is community social assistance and community development which is intended for teachers, preachers, and Al-Qur'an preachers who have served in the world of education and da'wah for at least 3 years in village or rural area. In this study using the Analytical Hierarchy Process (AHP) method for weighting criteria so as to produce a comparative assessment of the teacher's sympathetic criteria consistent and does not require an assessment revision and Simple Additive Weighting (SAW) for ranking so that the teachers who deserve assistance are the first priority teacher 1, teacher 3, teacher 5 and teacher 9.